Government of Rajasthan Five Year Plan 2012-2017 (Draft) Volume-II Physical and Financial Tables - Planning Commission (Planning Commission, 2012)
Proposed Outlays - Major Heads / Minor Heads of Development , Proposed Outlays - Major Heads / Minor Heads of Development: From State Budget, State PSE's and Local Bodies , Proposed Outlays - Major Heads / Minor Heads of Development - For Rural and Urban Local Bodies , Proposed Outlay for Ongoing and New Schemes , Physical Targets And Achievements , Statement Regarding Externally Aided Projects , Centrally Sponsored Schemes , Tribal Sub Plan (TSP) : Financial Outlays , Special Component Plan For Scheduled Castes (SCSP -1) - Financial Outlays , Financial Outlays / Expenditure For Voluntary Sector , Women Component in the State Plan Programmes : Financial Outlays , Information related to Flagship Programmes
Physical and Financial Tables
Government of Rajasthan